The Planck Constant for the Definition and Realization of the Kilogram. Issue 5 (27th December 2018) - Wood, Barry; Bettin, Horst
Abstract: On May 20, 2019 the values of the Planck, h, and Avogadro, N A, constants will be fixed, revising our measurement system, the International System of Units (SI), and providing a new way to get mass traceability. While the famous energy relations mc 2 and hf may remind many that the Planck constant is indeed related to mass, it is less recognized how this is also true for the Avogadro constant. These concepts are reviewed in the context of the upcoming revision of the SI. How the fixed values were chosen and how mass traceability will be maintained with the smallest uncertainty are also discussed. Abstract : On May 20, 2019 the values of the Planck, h, and Avogadro, N A, constants will be fixed, revising our measurement system, the international system of units (SI) . How these constants are related to mass, how their fixed values are chosen and how mass traceability will be maintained with the smallest uncertainty are discussed.